2018
DOI: 10.3390/s18113805
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risk Prevention through Smartwatches: Precision and Uncertainty Effects of the Built-In Accelerometer

Abstract: Wearable technology has had a significant growth in the last years; this is particularly true of smartwatches, due to their potential advantages and ease of use. These smart devices integrate sensors that can be potentially used within industrial settings and for several applications, such as safety, monitoring, and the identification of occupational risks. The accelerometer is one of the main sensors integrated into these devices. However, several studies have identified that sensors integrated into smart dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 69 publications
(102 reference statements)
0
8
0
7
Order By: Relevance
“…An in-depth discussion of the IoT-ACRES hardware and software is not in the scope of this paper. The authors of [52] evaluate the use of wearable technologies and focus on smartwatches as these devices are becoming more common every day. After testing the smartwatches, the authors concluded that while they are affordable technology, they were not reliable devices for safety data acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…An in-depth discussion of the IoT-ACRES hardware and software is not in the scope of this paper. The authors of [52] evaluate the use of wearable technologies and focus on smartwatches as these devices are becoming more common every day. After testing the smartwatches, the authors concluded that while they are affordable technology, they were not reliable devices for safety data acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…The smartwatch used for the data collection was previously analyzed to identify its frequency response by using a methodology described in a previous work [ 85 ]. The analysis employs an adapted version of the calibration method by comparison with a reference accelerometer.…”
Section: Methodsmentioning
confidence: 99%
“…According to the methodology established in [ 85 ], an error band has been considered for amplitude and frequency linearity according to the specifications of the International Organization for Standardization (ISO) 8041:2005 [ 86 ], in which values with a deviation greater than ±6% are considered linearity errors.…”
Section: Methodsmentioning
confidence: 99%
“…The authors believed that there is great potential for the application of their proposed wearable insole pressure system, as it has both practical uses and economic benefits due to the usage of IoT technologies including sensors, vision-based technologies, and wireless communication. Sigcha et al [ 9 ] believed that wearable technology, such as microelectronic mechanical systems (MEMS), accelerometers, and smartwatches had witnessed tremendous evolution in the domain of safety research. Among these, smartwatches are easy to use and have broad applicability, e.g., integrating an accelerometer with a smartwatch for precise motion detection, and considering any uncertainty effects in the occupational risk assessment.…”
Section: Literature Reviewmentioning
confidence: 99%